Unexpected Diversity of Chloroplast Noncoding RNAs as Revealed by Deep Sequencing of the Arabidopsis Transcriptome - Hotto, Amber M. (Genetics Society of America, 2011)
Noncoding RNAs (ncRNA) are widely expressed in both prokaryotes and eukaryotes. Eukaryotic ncRNAs are commonly micro- and small-interfering RNAs (18–25 nt) involved in posttranscriptional gene silencing, whereas prokaryotic ncRNAs vary in size and are involved in various aspects of gene regulation. Given the prokaryotic origin of organelles, the presence of ncRNAs might be expected; however, the full spectrum of organellar ncRNAs has not been determined systematically. Here, strand-specific RNA-Seq analysis was used to identify 107 candidate ncRNAs from Arabidopsis thaliana chloroplasts, primarily encoded opposite protein-coding and tRNA genes. Forty-eight ncRNAs were shown to accumulate by RNA gel blot as discrete transcripts in wild-type (WT) plants and/or the pnp1-1 mutant, which lacks the chloroplast ribonuclease polynucleotide phosphorylase (cpPNPase). Ninety-eight percent of the ncRNAs detected by RNA gel blot had different transcript patterns between WT and pnp1-1, suggesting cpPNPase has a significant role in chloroplast ncRNA biogenesis and accumulation. Analysis of materials deficient for other major chloroplast ribonucleases, RNase R, RNase E, and RNase J, showed differential effects on ncRNA accumulation and/or form, suggesting specificity in RNase-ncRNA interactions. 5′ end mapping demonstrates that some ncRNAs are transcribed from dedicated promoters, whereas others result from transcriptional read-through. Finally, correlations between accumulation of some ncRNAs and the symmetrically transcribed sense RNA are consistent with a role in RNA stability. Overall, our data suggest that this extensive population of ncRNAs has the potential to underpin a previously underappreciated regulatory mode in the chloroplast.